(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
This article examines the pedagogical and methodological effectiveness of interactive methods in developing phonological awareness and phonetic knowledge among primary school pupils. The study focuses on learners’ ability to understand sound-letter relationships, distinguish vowels and consonants, segment words into syllables, perform simple phonetic analysis, and explain the connection between pronunciation and spelling. A quasi-experimental design was used with 64 second-grade pupils divided into an experimental group (n = 32) and a control group (n = 32). In the experimental group, phonetic topics were taught through brainstorming, cluster mapping, Venn diagrams, role-play, INSERT, pair analysis, and phonetic games, whereas the control group received instruction through conventional explanation, model-based exercises, and oral questioning. The results showed that the experimental group demonstrated a substantially higher increase in overall achievement, rising from 45.6% to 81.9%, compared with the control group, which increased from 48.1% to 62.5%. The post-test difference between the two groups was statistically meaningful, t(62) = 6.69, p < .001, Cohen’s d = 1.67. The findings suggest that interactive instruction strengthens not only phonetic knowledge but also pupils’ cognitive engagement, oral participation, independent reasoning, and self-monitoring.